Empowering knowledge and its connection to health-related quality of life: A cross-cultural study: A concise and informative title: Empowering knowledge and its connection to health-related quality of life - Koekenbier, Krista; Leino-Kilpi, Helena; Cabrera, Esther; Istomina, Natalia; Stark, Åsa Johansson; Katajisto, Jouko; Lemonidou, Chryssoula; Papastavrou, Evridiki; Salanterä, Sanna; Sigurdardottir, Arun; Valkeapää, Kirsi; Eloranta, Sini (My University, 2016)
Abstract AIMS: Assess the association between patient education (i.e. empowering knowledge) and preoperative health-related quality of life, 6months postoperative health-related quality of life, and the increase in health-related quality of life in osteoarthritis patients who underwent total hip or total knee arthroplasty. METHOD: This is a cross-cultural comparative follow-up study using structured instruments to measure the difference between expected and received patient education and self-reported health-related quality of life (EQ-5D) in Finland, Greece, Iceland, Spain and Sweden. RESULTS: The health-related quality of life was significantly increased 6months postoperatively in all countries due to the arthroplasties. In the total sample, higher levels of empowering knowledge were associated with a higher health-related quality of life, both pre- and postoperatively, but not with a higher increase in health-related quality of life. On the national level, postoperative health-related quality of life was associated with higher levels of empowering knowledge in Finland, Iceland and Sweden. The increase in health-related quality of life was associated with levels of empowering knowledge for Greece. CONCLUSIONS: Overall, it can be concluded that the level of empowering knowledge was associated with high postoperative health-related quality of life in the total sample, even though there is some variation in the results per country.
Keywords: Cross-cultural; Empowering knowledge; Empowerment; Health-related quality of life; Osteoarthritis; Patient-centered education